Expression of VEGFR2 and NRP-1 in non-small cell lung cancer and their clinical significance - Ding, Manhua; Liu, Liang; Hu, Chengxi; Liu, Yi; Qiao, Yun; Jiang, Xiaodong (Chinese Journal of Cancer Research; Vol 26, No 6 (December 30, 2014): Chinese Journal of Cancer Research, 2014)
Objective: Vascular-targeted therapy is gradually becoming more appealing for patients with lung cancer. It is unclear whether vascular endothelial growth factor receptor 2 (VEGFR2) and neuropilin-1 (NRP-1) can be biomarkers for clinical treatment. We aimed to investigate the expression levels of VEGFR2 and NRP-1 in human non-small cell lung cancer (NSCLC) and their clinical significance by observing patient prognosis. Methods: VEGFR2 and NRP-1 were assessed by immunohistochemistry (IHC) in 40 patients with NSCLC and in 10 patients with benign lesions of lung; kinase insert domain receptor (KDR) and NRP-1 copy number gain (CNG) was assessed by fluorescence in situ hybridization (FISH). The distributions of overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan-Meier method and compared between groups by log-rank test. Results: Rates of positive immunostaining for VEGFR2 and NRP-1 were 58% and 55%, respectively. KDR and NRP-1 CNG (+) were detected in 32.5% and 30% of tumors, respectively. Levels of both VEGFR2 and NRP-1 in lung tumors were significantly different than in the control tissue (χ2=11.22, P=0.001; χ2=9.82, P=0.001, respectively); similar results were obtained using CNGs (χ2=4.39, P=0.036; χ2=3.95, P=0.046, respectively). Statistically significant correlations were observed with histological grade, clinical TNM stage and the lymph node status (P0.05). VEGFR2 showed a strong correlation with NRP-1 (Rs=0.68, P=0.00); similar results were observed with KDR and NRP-1 CNG (Rs=0.32, P=0.04). Significant differences in OS and PFS were observed between the groups with higher VEGFR2 and NRP-1 and those with lower expression (P